Contributions Of Paulo Freire’s Pedagogy: An Analysis Of Pedagogical Projects Of Undergraduate Degrees Of The Federal Institute Of Education, Science And Technology Norte De Minas Gerais – Ifnmg To Teacher Training: Contributions of Paulo Freire’s Pedagogy: An analysis of Pedagogical Projects of Undergraduate Degrees of The Federal Institute Of Education, Science And Technology Norte de Minas Gerais – IFNMG to Teacher Training - Moreira dos Anjos, Hellen Vivian; Teixeira Amorim, Mônica Maria; Barreto Rodrigues, Fernando (Revista Desenvolvimento Social, 2021)
The main objective of this article is to analyze the curricular designs and the contribution of Paulo Freire’s thought in the Pedagogical Course Projects (PPCs) of Undergraduate Degrees offered by the Federal Institute of Education, Science and Technology North of Minas Gerais (IFNMG). The methodology used is of a qualitative nature, as research and document analysis were prioritized for a better understanding of the documents based on their curricular designs. The article is structured in two parts: the first part contemplates the discussion about teacher education, curriculum and counter - hegemony, with capitalist society as the stage for this analysis and Paulo Freire’s teacher education proposal as a counter-hegemonic paradigm, able to critically react to the dominant training models. In the second part, the analysis of the PPCs of the IFNMG Licentiateships was carried out, based on the identification of freirian categories in their course projects.